Computed Tomography Analysis of Nasal Anatomy in Dorsal Preservation Rhinoplasty. (26th August 2021) - Eravci, Fakih Cihat; Özer, Halil; Arbağ, Hamdi; Eryilmaz, Mehmet Akif; Aricigil, Mitat; Dündar, Mehmet Akif
Abstract: Background: Subdorsal septal resection and radix osteotomy are distinctive surgical steps in preservation rhinoplasty. Objectives: The aim of this study was to evaluate the nasal bone thickness, the level of the septal bony-cartilaginous junction (K area), and the distances of the frontal sinus and skull base from the transverse osteotomy line in the Turkish population by means of conventional computed tomography (CT). Methods: A retrospective evaluation was made of 203 consecutive preoperative paranasal CT scans of patients (classified in terms of age and gender) who had undergone rhinoplasty surgery between January 2020 and June 2021. The nasal bone thickness at the medial canthus level, and the distances between the transverse osteotomy line and the K area, the frontal sinus, and the cribriform plate were measured. Results: The mean measurements were similar in terms of age groups ( P  = 0.402, P  = 0.542, P  = 0.134 and P  = 0.276 for ages 18-30, 30-40, 40-50, and >50 years, respectively). The mean nasal bone thickness and the distance between the transverse osteotomy line and the K area showed statistical significance ( P  = 0.001 and P  = 0.001, respectively). In both genders, the mean distances between the transverse osteotomy line and the frontal sinus and the cribriform plate were similar ( P  = 0.921 and P  = 0.280, respectively). The nasal bone was thinner and the K area position more cephalic in females. Conclusions: CT plays an important role in preoperative planning. The need for resection of the ethmoid perpendicular bone may be greater in males when lowering the dorsal hump, and hence they may be more prone to skull base complications. It is therefore necessary to be more careful in the surgical stage of subdorsal septal excision in males.